Analisis Produktifitas Pada Mesin Empty Bunch Press Untuk Menaikkan Jumlah Oil Extraction Rendemen (OER) Minyak Kelapa Sawit - Radwitya, Erick; Nopriyanti, Marisa; Septiani, Nica (Politeknik Negeri Ketapang, 2023)
Empty Palm Oil Bunches (TTKS) or empty fruit bunches are one of the solid wastes produced by palm oil mills. Judging from the oil content, TTKS has the potential to be re-quoted. Empty Bunch Press machine, so as to produce oil before being pressed (oil before press) and oil after being pressed (oil after press) produced using this machine and knowing the factors that cause OER or low oil yields. The analysis of this calculation can result in an average % OER empty bunch press of 0.16% and a total % OER from the addition of an empty bunch press machine of 21.91% where in this case there is an additional OER using an empty bunch press machine. Without the use of an empty bunch press machine,%OER 21.17%. The results of the analysis show that extracting oil obtained from TTKS using an empty bunch press machine can increase the factory's OER of about 0.16% to processed FFB. The results of the analysis from June 14 to June 27 2022 OER of palm oil has decreased or is low due to factors such as the maturity level of the fruit, processing at the factory, and poor fruit quality